Cycloartane triterpenoids from Pseudolarix amabilis and their antiviral activity. (March 2020) - Zhao, Xiao-Tong; Yu, Mei-Hua; Su, Shi-Yun; Shi, Xun-Long; Lei, Chun; Hou, Ai-Jun
Abstract: Seven undescribed cycloartane triterpenoids, pseudolarnoids A−G, together with ten known ones, were isolated from the seeds of Pseudolarix amabilis (J. Nelson) Rehder. Their structures were elucidated on the basis of spectroscopic analysis, X-ray crystallography, and ECD data. Pseudolarnoids A−C are cycloartane triterpenoids with a unique 16 S, 23 R -spirolactone moiety. Pseudolarnoids F, G, and pseudolarolide C demonstrated potent antiviral effects on HSV-1 in vitro . Graphical abstract: Seven undescribed cycloartane triterpenoids, pseudolarnoids A−G, together with ten known ones, were isolated from Pseudolarix amabilis . Pseudolarnoids A−C are cycloartane triterpenoids with a unique 16 S, 23 R -spirolactone moiety. Some isolates demonstrated potent antiviral effects on HSV-1 in vitro . Image 1 Highlights: Seven undescribed cycloartane triterpenoids were isolated from Pseudolarix amabilis. Cycloartane triterpenoids with a unique 16 S, 23 R -spirolactone motif are reported. Some of the triterpenoids showed significant antiviral effects on HSV-1.